A new modified block iterative algorithm for uniformly quasi--asymptotically nonexpansive mappings and a system of generalized mixed equilibrium problems - Saewan, Siwaporn; Kumam, Poom (Fixed point theory and algorithms for sciences and engineering, 2011)
In this paper, we introduce a new modified block iterative algorithm for finding a common element of the set of common fixed points of an infinite family of closed and uniformly quasi--asymptotically nonexpansive mappings, the set of the variational inequality for an α-inverse-strongly monotone operator, and the set of solutions of a system of generalized mixed equilibrium problems. We obtain a strong convergence theorem for the sequences generated by this process in a 2-uniformly convex and uniformly smooth Banach space. Our results extend and improve ones from several earlier works. 2000 MSC: 47H05; 47H09; 47H10.[PUBLICATION ABSTRACT]